A Belated Guest (from Literary Friends and Acquaintance) - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Belated Guest (from Literary Friends and Acquaintance)" by William Dean Howells is a reflective account written in the late 19th century. This work is a literary reminiscence, highlighting the author$1 (Bs encounters with notable literary figures, notably Bret Harte, a prominent American author. The book captures the essence of Howells' experiences and observations, painting a vivid picture of the literary landscape of the time and the personalities that inhabited it. In this piece, Howells recounts his delightful week spent hosting Bret Harte, who was celebrated for his evocative stories set in California. Through a warm narrative, the text illustrates their interactions, emphasizing Harte's charming yet slightly chaotic nature, as he often arrived late to events and effortlessly captivated his hosts and fellow literati. Howells reflects on their conversations, Harte$1 (Bs keen observations, and his somewhat ironical perspective towards literary conventions and celebrated personalities. This account serves not only as a tribute to Harte$1 (Bs vibrancy as a guest but also as a commentary on the literary scene of his time, embodying a blend of reverence and lighthearted critique of the complexities surrounding literary fame and friendship. (This is an automatically generated summary.)s
Release date is 2004-10-22
Produced by David Widger
Keywords: American literature -- 19th century -- History and criticism; Authors, American -- 19th century -- Biography; Howells, William Dean, 1837-1920 -- Friends and associates